Knowledge, attitude and issues in practicing kangaroo mother care at home after discharge from a kangaroo mother care ward of a tertiary care hospital in central Lahore (Journal of Fatima Jinnah Medical University, 2023)
Background: Kangaroo mother care (KMC) is well known intervention in preterm care. Mothers gets training from health professionals to provide skin to skin care, breast feeding which helps in infections prevention and early discharge. It is required to inquire the mothers experience during home environment to promote this technique after discharge from hospital. This study focused on gaining the knowledge, attitude of unsupervised mothers practicing KMC at home and determine the most common issues faced by them.Subjects and methods: A cross-sectional study, conducted at KMC ward of the Department of Pediatrics, Unit-1, Services Institute of Medical Sciences (SIMS), Lahore from March 2020 to April 2021 after ethical approval. Hospitalized mothers of stable pre-term infants were taught KMC techniques by trained health care provider. After two weeks of discharge from hospital mothers were interviewed according to structured questionnaire by the trained doctor about their KMC knowledge, experience and issues faced at home.  Results: Out of 156 mothers 145 (92.9%) conducted KMC at home and 93 (59.6%) performed intermittent KMC during nighttime (p=0.001). 152 (97.4%) mothers felt good, 133 ( 85.3%) were comfortable and 122 (78.2% ) deemed the process safe for their babies. 82 (52.6%) felt ease with provided kits (p=0.032).120 (76,9%) husbands felt KMC was essential for their babies. 102 (65.4%) mothers were allowed by their husbands to do KMC at home (p=0.000) and 68 (43.6%) fathers sometimes performed KMC themselves (p=0.001). Family and friends were also supportive in 104 (66.7%) cases while 112 (71.8%) mothers felt the positive attitude of the community (p=0.000). 127 (81.4%) mothers were willing to recommend KMC to new mothers (p=0.019).Conclusion: Most of the mothers performed intermittent KMC at home. They were assisted by husband and family members to carryout KMC at home. They are willing to recommend it to new mothers.
Keywords: Kangaroo Mother Care; Perception; Attitude; Barrier